Salinity tolerance of Aegiceras corniculatum and Ceriops tagal in the coastal area of Karachi, Pakistan - Muhammad Ayyaz; Jafron Wasiq; Fuad Muhammad; Waqar Ahmed; Muhammad Yaseen; Maria Ashraf; Muhammad Abdul Rahman (BIORE Scientia Publisher, 2023)
Indus delta with its coastal zones is the most significant coastal environment in Pakistan for mangroves and associated ecosystems. Mangrove forests are important components for maintenance of ecosystems in severe environments. The purpose of the study is to assess the mangrove species' tolerance to salinity. Aegiceras corniculatum and Ceriops tagal (C. tagal) propagules were grown in pots with sandy soil and subirrigated with 25, and 50% nitrogen-fortified saltwater for this research. The propagules were procured from the Indus delta. We raised seedlings for six months as an experiment. Aegiceras corniculatum species behaved moderately in the greenhouse, whereas Ceriops tagal's growth maximum at a salinity of 50% seawater and declined as the salinity increased. Furthermore, Ceriops tagal a non-secretor, accumulated more sodium and chloride ions while severely restricting the availability of other ions. This species might therefore be used to repair intertidal ecosystems, which frequently get freshwater. During a six-month the experimental cultivation period, and measurements were taken of the seedlings' length, weight at planting, and number of leaves. Maximum growth was observed in 50% seawater, and as the salinity increased, it became worse. Three times a week, fresh water was provided to wash away the excess salt. It has been discovered that medium and large-sized propagules function better in a greenhouse environment than small-sized ones. In order for plant seeds to successfully reproduce, the environmental conditions in which they disseminate and settle must be suitable for them. For establishment and dissemination inside the greenhouse environment, the propagules of viviparous mangrove species appear optimal.